Effects of Tart Cherry Powder on Serum Uric Acid in Hyperuricemia Rat Model. (22nd July 2020) - Li, Ruirui; Tan, Yuefeng; Li, Yanxia; Zhu, Xia; Tang, Xinyao; Zhang, Lishi; Chen, Jinyao
Abstract : Hyperuricemia, as a critical risk factor for various adverse clinical outcomes, shows a trend of increasing prevalence among young-aged population. Dietary adjuvant therapy by function foods, such as tart cherry, is promising. Thus, effects of tart cherry powder specialized in hyperuricemia were explored via establishing a hyperuricemia model in Sprague Dawley rats by cotreatment with oteracil potassium and adenine. The results indicated that low dose of tart cherry powder (0.17 g/kg·bw) showed effects on hyperuricemia by slightly decreasing serum uric acid and improving kidney injury, whereas high dose of tart cherry powder (0.50 g/kg·bw) could merely alleviate kidney injury. Meanwhile, adenosine deaminase activity rather than xanthine oxidase activity was affected at low dose, which reveals low dose of tarty cherry powder may be beneficial to hyperuricemia through reduction of ADA activity, and its reported potentials on antioxidation or anti-inflammation provide clues for further study.